Methanol and Ethanol as Alternative Fuels for Shipping - Radonja, Radoslav; Bebić, Dragan; Glujić, Darko (Promet - Traffic&Transportation, 2019)
Over the past decade regulatory emission control has been adopted and even stricter emission reductions are being considered. In order to comply with the present and future regulations the ship owners and engine manufacturers are facing a difficult task. The shipping industry is presently offering multiple choices such as scrubbers and Selective Catalytic Reduction (SCR), dual fuel engines, Liquefied Natural Gas / Liquefied Petroleum Gas (LNG/LPG) powered engines, and lately the introduction of methanol and ethanol as alternative fuels. This work presents a short overview of the possible use of methanol and ethanol as lternative fuels in shipping. The first part of this work deals with physical properties of methanol and ethanol, production and availability, as well as advantages and disadvantages in comparison with other fuels. In the second part the cost perspective is presented together with the cost-benefit analysis, which is the most important aspect in the ship owner’s decision whether to invest into the new alternative. Methanol and ethanol are not magical solutions, but rather another alternative which, from the cost perspective, offers a potential under certain circumstances. These circumstances are competitive prices in comparison to Marine Gas Oil (MGO) and time spent in Emission Control Area (ECA) which should be a large portion of the total sailing time. In this paper the scientific methodology was followed by using the method of compilation, the descriptive and the comparative methods.